Risk assessment and management by cemeteries in Metropolitan Lima and Callao - Aranibar Tapia, Sonia Beatriz (2011)
Cemeteries are places where people put the cadavers for their inhumation. These places must count on technical and sanitarian conditions so that the human cadaver does not represent any risk for the workers of the cemeteries, for the population and for the environment; through the characteristic emission of the decomposition process of the corpses. The research objective is to identify and control the risks for the workers of the cemeteries, for the surrounding population and for the environment; with the aim of contributing to improving the current situation of the cemeteries. The investigation has been conducted through a not random and deliberated sample of six cemeteries located in Lima city. It includes three steps: information collection, risk assessment, information systematisation and analysis. Interviews and observations have been conducted. Risks have been assessed according to three levels: low, medium and high; having established health, welfare, sanitary and environmental criteria. 30% of the workers and 39% of the population who lives around the six cemeteries have been interviewed.